Epidemic of Histia Flabellicornis Ultima Hering (lepidoptera: Zygaenidae: Chalcosiinae) on Bischofia Javanica Blume (euphorbiaceae) in New forest, Dehradun, India - Singh, Sudhir; Faisal, Mohd. (Indian Forester, 2014)
No abstract